2022
DOI: 10.1039/d1tb02775a
|View full text |Cite
|
Sign up to set email alerts
|

Conformational-specific self-assembled peptides as dual-mode, multi-target inhibitors and detectors for different amyloid proteins

Abstract: Prevention and detection of misfolded amyloid proteins and their β-structure-rich aggregates are the two promising but differ-ent (pre)clinical strategies to treat and diagnose neurodegenerative diseases including Alzheimer’s diseases (AD) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As reported previously, diverse Ab scavengers, including small molecules, 12,13 proteins, 14 nanomaterials, 15,16 and peptides, 17,18 have been designed to modulate the on-pathway fibrillization. When compared with others, the scavengers based on nanomaterials display outstanding advantages, such as easy functionalization, desirable biodegradability, and high biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, diverse Ab scavengers, including small molecules, 12,13 proteins, 14 nanomaterials, 15,16 and peptides, 17,18 have been designed to modulate the on-pathway fibrillization. When compared with others, the scavengers based on nanomaterials display outstanding advantages, such as easy functionalization, desirable biodegradability, and high biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The worm results showed that ANP significantly inhibited AD-like symptoms of worm paralysis, suppressed Aβ deposits in the head region of the worms, and diminished ROS production caused by oxidative stress. From an amyloid inhibitor viewpoint in Figure , most of the peptide-based Aβ inhibitors , comprise short sequences with ≤10 residues, which exhibit some intrinsic disadvantages, including (i) limited inhibition efficiency (equimolar inhibitors only lead to <30% inhibition of Aβ aggregation), (ii) high concentrations (inhibitor: Aβ > 6:1), (iii) poor cell protection (∼20–60% of cell viability), or (iv) low binding affinity ( K D = 9–156 μM). , For comparison, peptide inhibitors with residues >10 are more efficient at inhibiting Aβ aggregation and toxicity, presumably due to their high enzymatic proteolysis resistance, high structural stability, and multiple reactive sites. For instance, equimolar antimicrobial peptides of defensins can inhibit 100% Aβ aggregation and thus rescue 35% of neuron cells, while a very small amount of SEVI (1 μM) can completely inhibit Aβ aggregation (20 μM) and increase cell viability by 40% .…”
Section: Introductionmentioning
confidence: 99%